2017
DOI: 10.5935/0034-7280.20170010
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Crosslinking: The Standard Protocol

Abstract: RESUMOO objetivo desta revisão é de determinar as indicações e eficácia da cirurgia que promove novas ligações covalentes entre as fibras de colágeno da córnea, conhecida como Cross-Linking (CXL), assim como esclarecer seus objetivos. O ceratocone é uma doença ectasica da córnea, bilateral, assimétrica, que, principalmente, cursa com encurvamento e afinamentos progressivo, e se inicia em geral na segunda década de vida. O uso primário do CXL tem sido na interrupção da progressão do Ceratocone. Apesar do conhec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
6
0
3
Order By: Relevance
“…Similarly, many authors have reported the good and lasting effect of standard CXL in comparison with AXL. In fact, it has been observed that AXL had a limited corneal flattening influence in topography while standard CXL had an excellent topographic corneal flattening outcome that led to keratoconus stability and postoperative visual improvement (Choi et al 2017;Kymionis et al 2017;Santhiago 2017). Brittingham et al (2014) stated that AXL has negative effect on the demarcation line at 12 months after cross-linking with increased steepening of the anterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, many authors have reported the good and lasting effect of standard CXL in comparison with AXL. In fact, it has been observed that AXL had a limited corneal flattening influence in topography while standard CXL had an excellent topographic corneal flattening outcome that led to keratoconus stability and postoperative visual improvement (Choi et al 2017;Kymionis et al 2017;Santhiago 2017). Brittingham et al (2014) stated that AXL has negative effect on the demarcation line at 12 months after cross-linking with increased steepening of the anterior corneal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the frequent side effects associated with the standard technique, new protocols are needed. 5 Line of sight loss, haze and progressive flattening are already well defined in research studies. Thus, we opted to adhere to pre-and postoperative keratometry measurements without studying other effects.…”
Section: Discussionmentioning
confidence: 91%
“…4 The physiopathology of corneal steepening is still unknown, but it is assumed that repetitive trauma, such as eye scratching, combined with abnormalities in the corneal connective tissue contribute to the progression of the disease. 5 ABCD classification is used to stage keratoconus from 0 to IV according to progression based on the posterior and anterior corneal curvature, corneal thickness, best corrected visual acuity and corneal scars. 6 Although there have been advances in knowledge, the aetiology of keratoconus has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations